Quantitative stereophotogrammetric & MRI evaluation of ankle articular cartilage and ankle joint contact characteristics - Millington, Steven Andrew (2008)
Osteoarthritis and degenerative cartilage diseases affect millions of people. Therefore, there is huge interest in developing new therapies to repair, replace and/or regenerate cartilage. This necessitates advances in techniques which make earlier non-invasive diagnosis and objective quantitative evaluations of new therapies possible. Most previous research has focused on the knee and neglected the ankle joint. Hence, the aims of this thesis are to describe and quantify the geometric properties of ankle cartilage, to evaluate joint contact characteristics and develop techniques which allow quantitative measurements to be made in vivo.